The assessment of influence of fatigue on quality of life lung cancer patients - Milaniak, Irena; Marczewska, Ewa (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Background. Evaluation of quality of life in patients with lung cancer is an important part of patient care during treatment. Lung cancer is the most common and the second most cancer  in Poland Despite significant progress in oncology, treatment of lung cancer does not give satisfactory results, mostly due to late diagnosis, old age patients and existing comorbidities. Aim of the study. The main aim of this study was to demonstrate the impact of fatigue on quality of life (QOL) lung cancer patients treated  with chemotherapy Material and methods. 100 patients were included in the study. The group was divided into 3 subgroups depending on the course of chemotherapy (I, III, IV course). The  QOL of lung cancer patients was measured using the WHO QOL Brief Questionnaire. To estimate fatigue level used a Brief Fatigue Inventory Scale. Data was statistically analyzed. Results and conclusion . Descriptive analyses showed decreased of overall quality of life in all subgroups, the worse was in the II group (III course). The mean domain scores of WHOQOL-BREF was worse in psychological domain, the best in social relations. There were statistical differences between groups. The incidence of fatigue for the group was 79%. The fatigue of patients was strongly negatively correlated with all domain of QOL.